PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK DENGAN MENGUNAKAN ICE BREAKING PADA ANAK KELOMPOK B DI TK NURUL HUDA BABAKAN TANGERANG - Yuniyarsih Yuniyarsih; Leni Nurmiyanti (stit-islamic-village, 2021)
Early childhood is a very sensitive period in the process of growth and development. Gross motor development in children is one of the developments that needs attention by all educators. on this research, researchers are interested in conducting research related to increasing children's gross motor skills, using ice breaker. Based on direct observations, the researchers witnessed the lack of a well-constructed stimulus in increasing gross motor skills, and the use of ice braking at the Nurul Huda Babakan Islamic Kindergarten was not yet maximal. This is a concern for researchers, because of the impact of the lack of media to express a movement, the alpha zone of children is not yet open when learning, of course, will reduce the absorption of the material presented. This study uses a Class Action Research method or what is often known as CAR. The researcher used two cycles in the research process to observe the data collection in the research. Before the first cycle was carried out, the researcher carried out the pre-cycle first. The results of this study indicate that children's gross motor skills can be increased through the provision of appropriate and appropriate ice breaker. The ice breaking used is of course ice breaking which can trigger an increase in children's gross motor skills. Based on the results of research conducted, the gross motoric development of children has increased in each cycle, the increase in research in cycle I to cycle II reached 5.5% from the results of the comparison of the two cycles.